DUAL MILITARY SOCIOLOGICAL ADVANTAGES TO CONFLICT WITH LIFESTYLE - Haque Bhuiyan, Md. Majidul (International Journal of Engineering Technologies and Management Research, 2022)
Bangladesh armed forces is a well known organization for its professionalism. Keeping forces goal 2030 in mind and to keep pace with the developed forces, Bangladesh armed forces is also upgrading itself in regards to men and equipments. As a part of this process, Bangladesh armed forces started inclusion of female officers since Jan 2000. Female officers are now getting involved in various operational and administrative activities in the units or bases along with their male colleagues. At the same time, many of the female officers are getting married with male officers, which gives them some sociological advantages. On the other hand, some challenges have also come up in dual military couples' life. The number of dual military couples are increasing day by day. Thereby, the challenges of dual military couples have become an organizational matter to address.